Penguatan Pendidikan Pesantren Pasca Penetapan Undang-Undang Nomor 18 Tahun 2019 Tentang Pesantren - Bazari Syam; Ade Fartini (Fakultas Syariah UIN Sultan Maulana Hasanuddin Banten, 2022)
The Indonesian constitution UUD 1945 has a mandate to educate the nation's citizens by upgrading the human resources through education and in particularly, that deals with the Law Nomor 20/2003 on National Education as a government effort to upgrade the education. The Indonesian education recognizes both formal education as well as an informal one. Pesantren Education as the oldest education institution in Indonesia has special and unique characteristics. Even though its existence has been so long time, however it still has a minor attention from the government. Since the Indonesian independence, the Pesantren has no special protection in which protects the Pesantren specifically in the Nasional Education Law System. There is only one chapter that mentions Pesantren so that it makes the problems and challenges collides each other due to the absence of exacting law. It is an essential for the government to make and validate the born of Law Nomor. 18, 2019 on Pesantren as an effort to give a big chance for Pesantren to maintain the quantity as well as the quality of the Pesantren in order to have competition and professional aspects, so that the Pesantren will be able to produce graduates amidst the Globalization Era, and come up with the better education quality services.